2022
DOI: 10.21037/acs-2022-rmvs-28
|View full text |Cite
|
Sign up to set email alerts
|

Robotic and endoscopic mitral valve repair for degenerative disease

Abstract: Background: Minimally invasive mitral valve repair has been proven to be a safe alternative to open sternotomy and may be accomplished through classic endoscopic and robotic endoscopic approaches.Outcomes across different minimally invasive techniques have been insufficiently described. We compare early and late clinical outcomes across matched patients undergoing robotic endoscopic and classic endoscopic repair.Methods: From 2011 to 2020, 786 patients underwent minimally invasive mitral surgery, from which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Finally, to our knowledge, this is the first study showing an independent association between robotic-assisted MV surgery and a reduction in postoperative myocardial injury; this may be due to several factors. The association between robotic-assisted mitral valve surgery and shorter aortic cross-clamp time is controversial; apart from one study [ 23 ], most studies reported significantly longer times for robotic techniques [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. We deem that the independent association with less myocardial injury might be related to the more precise and less traumatic heart incisions and manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to our knowledge, this is the first study showing an independent association between robotic-assisted MV surgery and a reduction in postoperative myocardial injury; this may be due to several factors. The association between robotic-assisted mitral valve surgery and shorter aortic cross-clamp time is controversial; apart from one study [ 23 ], most studies reported significantly longer times for robotic techniques [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. We deem that the independent association with less myocardial injury might be related to the more precise and less traumatic heart incisions and manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…As both techniques use comparable approach and cannulation techniques, little differences in early results are to be expected. The comparison of late results of both treatment approaches is lacking and very few reports with low patient numbers are available ( 21 ).…”
Section: Robotic Versus Port-access Mitral Valve Repairmentioning
confidence: 99%